The Body and Consent in Psychology, Psychiatry, and Medicine A Therapeutic Rape Culture. - Tosh, Jemma (Milton : Routledge, 2019)
This groundbreaking text interrogates the constructed boundary between therapy and violence, by examining therapeutic practice and discourse through the lens of a psychologist and a survivor of sexual abuse. It asks, what happens when those we approach for help cause further harm? Can we identify coercive practices and stop sexual abuse in psychology, psychiatry, and medicine? Tosh explores these questions and more to illustrate that many of the therapies considered fundamental to clinical practice are deeply problematic when issues of consent and sexual abuse are considered. The book examines a range of situations where medical power and authority produces a context where the refusals and non-consent of oppressed groups are denied, dismissed, or ignored, arguing that key concepts and discourses have resulted in the production and standardisation of a therapeutic rape culture in the helping professions. Tosh uses critical intersectionality theory and discourse analysis to expertly highlight the complex interrelationships between race, class, gender, sexuality, and disability in our understanding of abuse and how we define survivors. Drawing on a wide range of comprehensive examples, including experiences and perspectives from cisgender and transgender men and women, as well as nonbinary and intersex people, this is essential reading for students and researchers of critical and queer psychology, gender studies, as well as mental health practitioners and social workers.
Cover; Half Title; Title; Copyright; Dedication; CONTENTS; Acknowledgements; 1 Introduction; 2 Intersex youth: non-consensual surgeries and nosocomial sexual abuse; 3 Queer and trans youth: 'sexual rehearsal play' and reparative therapies; 4 'Sex' as treatment: consent, coercion, and sex therapy; 5 Penetration as 'treatment': the pathologisation of sexual avoidance and pain; 6 Phallometrics: quantifying sexuality and sexual violence; 7 Conclusions: a therapeutic rape culture; References; Index
Description based upon print version of record.
OCLC-licensed vendor bibliographic record.
Keywords: PSYCHOLOGY / General; Clinical psychology; Sex crimes -- Psychological aspects